MODEL OPTIMASI PENGELOLAAN INVENTARIS ASET BERBASIS WEB MENGGUNAKAN PENDEKATAN DESIGN THINKING - Ardi, Abdullah (Universitas Teknokrat Indonesia, 2025)
Effective asset inventory management is a critical challenge for government agencies, including the Secretariat Office of Barito Kuala Regency. Inefficiencies in this process often result in inaccuracies in record-keeping, delays in reporting, and difficulties in real-time asset tracking. This study aims to develop an optimized web-based asset inventory management model by applying the Design Thinking approach to address these issues. Through the Empathize phase, it was identified that the error rate in asset record-keeping reached 25%, reporting delays extended up to 72 hours, and 35% of assets could not be tracked in real-time. In the Define phase, these issues were formulated into a need for a more accurate, efficient, and real-time accessible asset management system. The proposed solutions included the development of a web-based record-keeping system, a real-time tracking module utilizing Radio-Frequency Identification (RFID) technology, and an automated reporting feature integrated with the audit system. Testing results indicated that the new system successfully reduced record-keeping errors by 90%, shortened reporting times from 72 hours to 6 hours, and improved asset tracking efficiency by 83.3%. Users provided positive feedback, with the system achieving an average System Usability Scale score of 84.5, classified as